Convergence of Generalized Lupaş-Durrmeyer Operators - Mohd Qasim; Mohammad Mursaleen; Asif Khan; Zaheer Abbas (Mathematics, 2020)
The main aim of this paper is to establish summation-integral type generalized Lupaş operators with weights of Beta basis functions which depends on <semantics> μ </semantics> having some properties. Primarily, for these new operators, we calculate moments and central moments, weighted approximation is discussed. Further, Voronovskaya type asymptotic theorem is proved. Finally, quantitative estimates for the local approximation is taken into consideration.